Implementasi Kebijakan Pengelolaan Aset Daerah: Kajian Pengelolaan Aset Daerah Dan Barang Milik Daerah Berdasarkan Permendagri Nomor 19 Tahun 2016 oleh Badan Pengelolaan Aset Daerah/BPAD - Rahmad Purwanto W; Christine Diah Wahyuningsih; Rina Nuraini Selly (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Good management of regional assets or regional property as a strategic policy for regional officials. Good and accountable regional asset management means that OPD will receive funding sources to finance development in the region. In managing regional assets, regional governments must pay attention to planning needs for budgeting, procurement, receipt, storage and distribution, use, administration, utilization, security and maintenance, assessment, write-off, transfer, guidance, supervision and control, financing. The entire asset management process is in order to achieve management objectives in an efficient and effective manner so that regional wealth can be used in public services and obtain regional (non-tax) income. Implementing regional needs planning and regional governments preparing Regional Asset Balances (NAD) as part of implementing good and accountable governance.